Teacher Administrative Burden On Burnout Tendencies For Early Childhood Teachers - Elvina, Nadira; Rahmatika, Wegidia Chaisa; Kumala Dewi, Nurul Fitria (JUPE : Jurnal Pendidikan Mandala, 2026)
High administrative burdens, such as preparing learning materials, managing student documents, and reporting learning, have the potential to cause prolonged work stress and impact teachers' psychological well-being. This study used a quantitative approach with a correlational design. The subjects were all 30 early childhood education (PAUD) teachers in Karang Tengah District, Tangerang City, selected using a total sampling technique. Data collection was conducted through questionnaires to measure the level of administrative burden and teacher burnout tendencies. The data obtained were analyzed descriptively and correlationally. The results showed that teachers' administrative burden was in the moderately high category and had a positive relationship with burnout tendencies in early childhood teachers. The higher the perceived administrative burden, the higher the tendency for burnout, which is characterized by emotional exhaustion, decreased work motivation, and reduced energy in carrying out learning tasks. Thus, it can be concluded that this study confirms that administrative burden is a significant factor contributing to burnout in early childhood teachers. Therefore, efforts are needed from schools and education policymakers to manage and simplify teachers' administrative burdens to maintain teacher mental well-being and improve the quality of early childhood learning.